Impact of Phosphodiesterase-3 Inhibitor and Prostacyclin Analogue Combination on Pulmonary Hemodynamics in Acyanotic Congenital Heart Disease Patients with Pulmonary Hypertension: A Randomized Controlled Trial - Sefri Noventi Sofia; Bahrudin; Ignatius Riwanto; Anindita Soetadji; Hardhono; Muhammad Thifan Satyagraha (International Journal of Biomedicine)
Background: Acyanotic congenital heart disease (ACHD) with left-to-right shunting frequently presents with pulmonary hypertension (PH), especially in developing countries where treatment options are often limited and costly. Cilostazol, a phosphodiesterase-3 inhibitor, has vasodilatory and inotropic effects, but its impact on pulmonary vascular resistance (PVR) and pulmonary blood flow (Qp) in this condition remains unclear. The aim of this study was to evaluate the effect of adding cilostazol to standard beraprost therapy on PVR and Qp in patients with ACHD complicated by PH. Methods and Results: This double-blind randomized controlled trial involved 40 subjects with ACHD and PH. Participants were assigned to receive either cilostazol plus beraprost or placebo plus beraprost for three months. In the cilostazol+beraprost group, PVR significantly decreased from 11.1±11.8 to 10.1±10.9 Wood units (P=0.001), while Qp showed no significant change (11.5±6.49 vs. 13.3±9.34; P=0.128). The beraprost-only group showed a smaller decrease in PVR (11.1±13.2 vs. 10.6±12.8; P=0 .006), but a significant increase in Qp (15.9±17.6 vs. 17.1±18.8; P=0.007). The E/e ratio for right ventricle diastolic function improved significantly only in the combination group. Conclusion: Adding cilostazol to beraprost reduces pulmonary artery pressure without significantly increasing pulmonary blood flow, possibly by improving right ventricular diastolic function in ACHD patients with PH.